Evaluating Vitamin D Status in Pre- and Postmenopausal Type 2 Diabetics and Its Association with Glucose Homeostasis. (2nd April 2018) - Fondjo, Linda Ahenkorah; Sakyi, Samuel Asamoah; Owiredu, William K. B. A.; Laing, Edwin Ferguson; Owiredu, Eddie-Williams; Awusi, Ebenezer Kwesi; Ephraim, Richard K. D.; Kantanka, Osei Sarfo
Abstract : Background . Type 2 Diabetes Mellitus (T2DM) and menopause are associated with vitamin D status. Oestrogen decline during menopausal stages promotes hypovitaminosis D. However, the interplay between vitamin D, menopause, lifestyle, and T2DM cannot be overlooked. This study assessed vitamin D status among pre- and postmenopausal T2DM women and determined its association with glycemic control and influence of lifestyle habits on hypovitaminosis D. Methods . This cross-sectional study was conducted at the Komfo Anokye Teaching Hospital, Kumasi, Ghana. Structured questionnaires were administered to 192 T2DM women; blood samples were collected for estimation of 25(OH) D and insulin using ELISA. Fasting blood glucose (FBG), lipid profile, glycated haemoglobin (HbA1c), and calcium were measured. Statistical analyses were performed using Graphpad Prism 6. Results . The prevalence of vitamin D inadequacy was 92.2%. Hypovitaminosis D was more prevalent among the postmenopausal T2DM women (63.8% versus 58.2%). Hypovitaminosis D significantly associated with insulin [R 2 = 0.01760, p = 0.0008 ], HbA1c [R 2 = 0.3709, p = < 0.0001 ], and FBG [R 2 = 0.3465, p = 0.0001 ] in only the postmenopausal women. Conclusion . Vitamin D deficiency is prevalent in pre- and postmenopausal T2DM but higher among postmenopausal women. Adequate vitamin D levels in both groups were associated with improved glucose control while hypovitaminosis D in the postmenopausal women was related to poorer glucose control. Vitamin D screening should be incorporated into management plan for T2DM to serve as an early tool for prevention of vitamin D deficiency.